Analysis of Midterm Outcomes of Endovascular Aneurysm Repair in Octogenarians From the ENGAGE Registry. (October 2020) - Mwipatayi, Bibombe P.; Oshin, Olufemi A.; Faraj, Joseph; Varcoe, Ramon L.; Wong, Jackie; Becquemin, Jean-Pierre; Riambau, Vincente; Böckler, Dittmar; Verhagen, Hence J.
Purpose: To assess periprocedural results and secondary endovascular procedure outcomes over 5 years in patients aged ≥80 vs <80 years undergoing endovascular aneurysm repair (EVAR). Materials and Methods: Data from the Endurant Stent Graft Natural Selection Global post-market registry (ENGAGE) were used for the analyses. A total of 1263 consecutive patients were enrolled in the prospective, observational, single-arm registry and divided into 2 groups according to age: ≥80 years (290, 22.9%) and <80 years (973, 77.1%). Baseline patient characteristics, risk scores according to the Society for Vascular Surgery (SVS) reporting standards, American Society of Anesthesiologists (ASA) classification, quality of life assessments [EuroQol 5 (EQ5D) index], and treatment outcomes, including all-cause mortality, aneurysm-related mortality, major adverse events, secondary endovascular procedures, and endoleaks were compared between groups. Results: Octogenarians were classified into the highest category of the SVS risk stratification system; however, this did not result in a significant difference in the 30-day mortality [1.4% (4/290) vs 1.2% (12/973) for controls; p=0.85] or major adverse event rates [5.2% (15/290) vs 3.6% (35/973), p=0.23]. Multivariable analysis confirmed that age ≥80 years, pulmonary disease, large aneurysm diameter, and renal insufficiency were significantly associated with all-cause mortality, whereas diameter was the only parameter associated with increased aneurysm-related mortality. The differences in freedom from secondary endovascular procedures over 5 years between octogenarians and controls did not reach statistical significance (88.5% vs 83.2%, p=0.07). Conclusion: EVAR can be performed in individuals aged ≥80 years with no statistically significant difference in midterm aneurysm-related deaths compared with younger patients. The findings in this elderly patient cohort show that EVAR can be safely performed with acceptable morbidity rates in octogenarians.